The Relationship Between the Use of Mobile Social Media and Subjective Well-Being: The Mediating Effect of Boredom Proneness - Bai, Jie; Mo, Kunyu; Peng, Yue; Hao, Wenxuan; Qu, Yuanshan; Lei, Xiuya; Yang, Yang (Frontiers in Psychology, 2021)
Objective This study took users of short-form mobile videos as research participants to explore the role of their boredom proneness in mediating the relationship between the use of mobile social media (UMSM) and subjective well-being (SWB). Methods A sample of 656 users was evaluated by the Problematic Mobile Social Media Usage Assessment Questionnaire, General Well-Being Schedule, and Boredom Proneness Scale. Results Firstly, significant interactions were found between monthly living expenses and the UMSM of the participants, which were recognized as factors affecting SWB. Secondly, the level of living expenses had little effect on the high-level and low-level groups of the UMSM but imposed a significant impact on the medium-level group. Thirdly, the UMSM showed an influence that could positively predict boredom; both the UMSM and boredom demonstrated a negative predictive effect on SWB. Conclusion The findings indicate that the inappropriate use of mobile social media negatively affects users’ subjective well-being; boredom partially mediated the relationship between the use of mobile social media and SWB.